High-Resolution Computed Tomography of Fibrotic Interstitial Lung Disease - Rodriguez, Karen; Ashby, Christian L.; Varela, Valeria R.; Sharma, Amita (Seminars in Respiratory and Critical Care Medicine, 2022)
While radiography is the first-line imaging technique for evaluation of pulmonary disease, high-resolution computed tomography (HRCT) provides detailed assessment of the lung parenchyma and interstitium, allowing normal anatomy to be differentiated from superimposed abnormal findings. The fibrotic interstitial lung diseases have HRCT features that include reticulation, traction bronchiectasis and bronchiolectasis, honeycombing, architectural distortion, and volume loss. The characterization and distribution of these features result in distinctive CT patterns. The CT pattern and its progression over time can be combined with clinical, serologic, and pathologic data during multidisciplinary discussion to establish a clinical diagnosis. Serial examinations identify progression, treatment response, complications, and can assist in determining prognosis. This article will describe the technique used to perform HRCT, the normal and abnormal appearance of the lung on HRCT, and the CT patterns identified in common fibrotic lung diseases.
Keywords: interstitial lung disease; high-resolution computed tomography; fibrosis; traction bronchiectasis; honeycombing; fibrotic sarcoidosis